2009
DOI: 10.2169/internalmedicine.48.1794
|View full text |Cite
|
Sign up to set email alerts
|

Polyethylene Glycol Interferon .ALPHA.-2b-induced Immune-mediated Polyradiculoneuropathy

Abstract: Polyethylene glycol-interferon α (PEG-IFNα) has been used as the standard treatment for hepatitis C virus (HCV) infection. There have been no previous reports of polyradiculoneuropathy with anti-ganglioside antibodies induced by PEG-IFNα-2b. We report a 59-year-old man who developed polyradiculoneuropathy during treatment with PEG-IFN α-2b for chronic HCV infection. Serum levels of anti-asialo-GM1 (GA1) and anti-GM1 antibodies were elevated. Cessation of therapy with double filtration plasmapheresis resulted i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Nevertheless, seven distinct cases of CIDP have been reported after the administration of a variety of IFNα species, including IFNα (6-9), pegIFN α-2a (10), and pegIFN α-2b (11,12). The interval between the administration of IFNα and the onset of CIDP ranged from 3 weeks to 11 months.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, seven distinct cases of CIDP have been reported after the administration of a variety of IFNα species, including IFNα (6-9), pegIFN α-2a (10), and pegIFN α-2b (11,12). The interval between the administration of IFNα and the onset of CIDP ranged from 3 weeks to 11 months.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, however, a favorable outcome was reported in all of the reported cases of IFNα-induced CIDP when the patients were treated with any of the standard therapies for CIDP, including oral steroids (6,8), plasma exchange (7,11), or IVIG (8)(9)(10)12). In the present case, three courses of IVIG were administered, but no maintenance immunomodulatory therapy was needed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Electrodiagnostic studies were compatible with a demyelinating process; some nerves showed multifocal conduction blocks [51,53,54,57]. Serum of 1 patient with CIDP showed presence of cryoglobulins and elevated anti-GA1/anti-GM1 antibody titers [56]. Nerve biopsies showed primary demyelination with [56] or without axonal degeneration, and without vasculitis [53,55,56].…”
Section: Interferon Alphamentioning
confidence: 94%
“…Serum of 1 patient with CIDP showed presence of cryoglobulins and elevated anti-GA1/anti-GM1 antibody titers [56]. Nerve biopsies showed primary demyelination with [56] or without axonal degeneration, and without vasculitis [53,55,56]. IFNα therapy was discontinued in all patients, but CIDP progressed for weeks thereafter [50,51,57].…”
Section: Interferon Alphamentioning
confidence: 97%